Transition metal anchored single-layer copper indium diphosphorus hexasulfur nanosheet as well as preparation method and application of transition metal anchored single-layer copper indium diphosphorus hexasulfur nanosheet
By anchoring the transition metal on the single-layer CuInP2S6 nanosheets, the problem of low catalytic hydrogen generation efficiency of single-layer CuInP2S6 nanosheets is solved by using hydrothermal method and calcining steps, and its performance in photocatalytic hydrogen evolution is significantly improved.
Patent Information
- Application Number
- CN202510167675.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-17
- Publication Date
- 2025-03-28
AI Technical Summary
The single-layer CuInP2S6 nanosheets are inefficient in catalytic hydrogen generation, mainly due to the weak adsorption ability of atoms on their surface and lower surfaces to hydrogen ions.
The transition metal is anchored on a single-layer CuInP2S6 nanosheet by hydrothermal method to form a single-layer CuInP2S6 nanosheet anchored by transition metal. The method includes mixing a single layer of CuInP2S6 nanosheets with a transition metal salt solution, performing a hydrothermal reaction, and then calcining under a protective atmosphere to obtain the anchored nanosheets.
By anchoring the transition metal, the adsorption capacity of nanosheets to hydrogen ions is significantly improved and its efficiency in photocatalytic hydrogen evolution is improved. The anchored Fe and Cr systems exhibit lower hydrogen adsorption free energy, especially the Fe-anchored system, whose hydrogen adsorption free energy reaches 0.05 eV, significantly improving the hydrogen evolution performance.
Smart Images

Figure CN119702026A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photocatalytic hydrogen evolution, and in particular to a transition metal-anchored single-layer CuInP2S6 nanosheet and a preparation method and application thereof. Background Art
[0002] Energy shortage, environmental pollution and the resulting climate change are huge challenges facing mankind today. The only way to solve these global crises is to develop sustainable clean energy, including solar energy, wind energy, hydropower, etc. Hydrogen energy is considered to be a sustainable energy source to solve the growing energy crisis and environmental problems. The only waste gas produced after hydrogen combustion is water vapor. And hydrogen can be obtained by photolysis of water, which is the most environmentally friendly hydrogen evolution process that converts solar energy into chemical energy in the form of hydrogen. Photocatalytic technology has broad application prospects due to its green, pollution-free and low energy consumption. Therefore, people are committed to developing photocatalytic materials with excellent catalytic properties. Precious metal-based materials, such as Pt, are considered to be ideal catalysts for hydrogen evolution reaction (HER) in a wide pH range of 0~14. However, the high cost and limited reserves limit the industrialization of metal platinum.
[0003] Two-dimensional ferroelectric materials can generate a permanent polarization electric field due to their inherent spontaneous dipole moment, which can be used as a direct driving force to achieve spatial separation and rapid transfer of carriers from the bulk material surface, thereby enhancing the photocatalytic hydrogen evolution activity. Ferroelectrics with out-of-plane polarization can achieve vertical polarization reversal, which is easier to control in practical applications and more likely to be used in device design and regulation.
[0004] A class of transition metal sulfide phosphides (MPTs) M1M2P2X6 (M1 = Cu / Ag, M2 = In / Bi, X = S / Se) has attracted widespread attention due to its out-of-plane ferroelectricity. Among them, only CuInP2S6 exhibits stable out-of-plane ferroelectricity at room temperature, and CuInP2S6 is the first experimental report to achieve room-temperature ferroelectricity in ultra-thin sheets (4nm). Since the single-layer CuInP2S6 itself has a wide energy band and the position of the band edge meets the conditions of redox potential, this single-layer CuInP2S6 is expected to become a catalyst for photocatalytic water splitting to produce hydrogen. However, problems such as low catalytic efficiency have hindered its application in related aspects. Therefore, how to seek a single-layer CuInP2S6 with high catalytic activity and its preparation method through material modification methods has become a technical problem that needs to be solved urgently in this field. Summary of the invention
[0005] The purpose of the present invention is to provide a transition metal-anchored single-layer CuInP2S6 nanosheet and its preparation method and application, so as to solve the problem that the S, P atoms on the upper surface layer and the S, P, Cu atoms on the lower surface layer and the exposed In sites of the single-layer CuInP2S6 nanosheet have very weak adsorption of hydrogen ions, resulting in low hydrogen evolution efficiency.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The present invention provides a method for preparing a transition metal-anchored single-layer CuInP2S6 nanosheet, which is characterized by comprising the following steps: 1) Mixing a single-layer CuInP2S6 nanosheet dispersion with a transition metal salt solution, and performing a hydrothermal reaction to obtain an intermediate product; 2) The intermediate product is calcined under a protective atmosphere to obtain a transition metal-anchored single-layer CuInP2S6 nanosheet.
[0007] Optionally, the single-layer CuInP2S6 nanosheet dispersion is prepared by dispersing the single-layer CuInP2S6 nanosheet in water; the dosage ratio of the single-layer CuInP2S6 nanosheet to water is 8-12 mg: 20 mL.
[0008] Optionally, the concentration of the transition metal salt solution is 1-5 mg / mL; The usage ratio of the transition metal salt solution and the single-layer CuInP2S6 nanosheet is 0.01-0.1 mL: 10 mg.
[0009] Optionally, the anchoring amount of the transition metal atoms in the single-layer CuInP2S6 nanosheet is 1-2%.
[0010] Optionally, the temperature of the hydrothermal reaction is 160-240° C., and the time is 3-8 h.
[0011] Optionally, the protective atmosphere comprises argon, nitrogen or helium; The calcination temperature is 3-8 °C / min, the temperature is 200-400 °C, and the calcination time is 0.5-3 h.
[0012] Optionally, the single-layer CuInP2S6 nanosheet dispersion and the transition metal salt solution are mixed at room temperature for 4 to 8 hours.
[0013] Optionally, the transition metal salt solution comprises a transition metal chloride salt solution or a transition metal acid salt solution.
[0014] The present invention also provides a transition metal-anchored single-layer CuInP2S6 nanosheet prepared by the preparation method of the above-mentioned transition metal-anchored single-layer CuInP2S6 nanosheet.
[0015] The present invention also provides the use of the above-mentioned transition metal-anchored single-layer CuInP2S6 nanosheet in a photocatalytic hydrogen evolution catalyst.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a transition metal-anchored single-layer CuInP2S6 nanosheet, which uses a transition metal anchoring method to affect the adsorption capacity of the surface atoms of the nanosheet to hydrogen ions, thereby improving the activity of the hydrogen production catalyst. According to the hydrogen evolution performance test, for the system with Fe anchored on the lower surface, the hydrogen adsorption free energy ( ) reached the optimal value among the prepared materials, which is 0.05 eV, followed by the system with Cr anchored on the lower surface, whose hydrogen adsorption free energy ) reaches 0.11 eV, and the best hydrogen adsorption free energy of the unanchored single-layer CuInP2S6 nanosheet is 0.94 eV. The hydrogen evolution performance of the anchored CuInP2S6 nanosheet is significantly improved. At the same time, the preparation process of transition metal anchoring is relatively simple and easy to implement, and the content of transition metals on the earth is also relatively abundant. Therefore, the present invention is of great significance both in terms of hydrogen evolution efficiency and preparation process.
[0017] The present invention uses a hydrothermal method to anchor transition metals to CuInP2S6 nanosheets. Compared with high-temperature calcination, hydrolysis precipitation, and sol-gel methods, the hydrothermal method has milder reaction conditions, and anchoring can be completed below 250°C, which is environmentally safe and conducive to reducing energy consumption. The anchoring of elements and the growth of CuInP2S6 crystals can be achieved simultaneously, and the agglomeration of powders can be effectively avoided. The calcination process removes impurities and volatile substances that may be contained in the intermediate product, making it drier and more stable. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 is the hydrogen adsorption free energy diagram of single-layer CuInP2S6 nanosheet; Figure 2 This is the hydrogen adsorption free energy diagram of the transition metal anchored monolayer CuInP2S6 nanosheet system, where the upper arrow indicates anchoring on the upper surface of the monolayer CuInP2S6 nanosheet, and the lower arrow indicates anchoring on the lower surface of the monolayer CuInP2S6 nanosheet. DETAILED DESCRIPTION
[0019] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0020] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0021] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0022] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.
[0023] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0024] Unless otherwise specified, the "room temperature" or "normal temperature" mentioned in the present invention is 25±2°C.
[0025] The present invention provides a method for preparing a transition metal-anchored single-layer CuInP2S6 nanosheet, which is characterized by comprising the following steps: 1) Mixing a single-layer CuInP2S6 nanosheet dispersion with a transition metal salt solution, and performing a hydrothermal reaction to obtain an intermediate product; 2) The intermediate product is calcined under a protective atmosphere to obtain a transition metal-anchored single-layer CuInP2S6 nanosheet.
[0026] In the present invention, step 1) solid-state reaction is used to synthesize high-quality bulk CuInP2S6, 8-15 mg of the synthesized bulk is dispersed in 30 mL of water, ultrasonically treated for 4-8 h, and then the supernatant is collected; the obtained liquid is dried at 50-100° C. for 36-48 hours to obtain a single-layer CuInP2S6 nanosheet.
[0027] In the present invention, after the hydrothermal reaction in step 1) is completed, the sample obtained is collected by centrifugation and completely dried, and the final product is washed with water and anhydrous ethanol for several times and vacuum dried at 50-70° C. for 16-28 hours.
[0028] In the present invention, the concentration of the transition metal salt solution is 1 to 5 mg / mL, preferably 1.5 to 4.5 mg / mL, more preferably 2 to 4 mg / mL, and most preferably 3 mg / mL; The usage ratio of the transition metal salt solution and the single-layer CuInP2S6 nanosheet is 0.01-0.1 mL:10 mg, preferably 0.02-0.08 mL:10 mg, further preferably 0.03-0.06 mL:10 mg, and further preferably 0.04-0.05 mL:10 mg.
[0029] In the present invention, the anchoring amount of the transition metal atoms in the single-layer CuInP2S6 nanosheet is 1-2%, preferably 1.2-1.8%, more preferably 1.3-1.6%, and further preferably 1.4-1.5%; When the percentage of transition metal atoms anchored is less than 1%, the anchored atoms cannot improve the hydrogen evolution rate. When it is greater than 2%, the hydrogen evolution efficiency will decrease. Therefore, controlling the anchoring amount of transition metal atoms in the single-layer CuInP2S6 nanosheet to 1-2% can significantly improve the hydrogen evolution rate. The atomic content of the transition metal is calculated as follows: For example, when the transition metal is Fe, the calculation formula is: 100%×Fe / (Cu+Fe).
[0030] In the present invention, the temperature of the hydrothermal reaction is 160-240°C, preferably 180-220°C, more preferably 190-210°C, most preferably 200°C, and the time is 3-8 h, preferably 4-7 h, more preferably 5-6 h, most preferably 5 h.
[0031] In the present invention, the protective atmosphere comprises argon, nitrogen or helium, preferably argon or nitrogen, most preferably argon; The calcination temperature is 3-8 °C / min, preferably 4-7 °C / min, more preferably 5-6 °C / min, the temperature is 200-400 °C, preferably 220-380 °C, more preferably 240-350 °C, more preferably 250-300 °C, most preferably 300 °C, and the calcination time is 0.5-3 h, preferably 1-2.5 h, more preferably 1.5-2 h, and most preferably 1 h.
[0032] In the present invention, the single-layer CuInP2S6 nanosheet dispersion is prepared by dispersing single-layer CuInP2S6 nanosheets in water; the dosage ratio of single-layer CuInP2S6 nanosheets to water is 8-12 mg:20 mL, preferably 9-11 mg:20 mL, and most preferably 10 mg:20 mL.
[0033] In the present invention, the single-layer CuInP2S6 nanosheet dispersion and the transition metal salt solution are mixed at room temperature for 4 to 8 h, preferably 5 to 7 h, and most preferably 6 h.
[0034] In the present invention, the transition metal includes chromium, manganese, iron or cobalt, etc., preferably iron or chromium.
[0035] The transition metal salt solution comprises a transition metal chloride salt solution or a transition metal acid salt solution; The transition metal chloride solution comprises chromium chloride, manganese chloride, iron chloride or cobalt chloride, etc., preferably chromium chloride or iron chloride; The acid salt solution of the transition metal comprises chromium sulfate, manganese sulfate, iron sulfate or cobalt sulfate, preferably chromium sulfate or iron sulfate.
[0036] The present invention also provides a transition metal-anchored single-layer CuInP2S6 nanosheet prepared by the preparation method of the above-mentioned transition metal-anchored single-layer CuInP2S6 nanosheet.
[0037] The present invention also provides the use of the above-mentioned transition metal-anchored single-layer CuInP2S6 nanosheet in a photocatalytic hydrogen evolution catalyst.
[0038] The raw materials used in the following examples of the present invention are all commercially available.
[0039] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention. Example 1
[0040] High-quality bulk CuInP2S6 was synthesized by solid-state reaction. 10 mg of the synthesized bulk was dispersed in 30 mL of deionized water and ultrasonicated for 6 h, after which the supernatant was collected. The obtained liquid was dried at 70 °C for 40 h to obtain a single-layer CuInP2S6 nanosheet. 10 mg of single-layer CuInP2S6 nanosheets were dissolved in 20 mL of deionized water by ultrasound, and then 0.06 mL of 3 mg / mL FeCl3 aqueous solution was added to the solution and stirred thoroughly. The obtained mixed solution was transferred to a Teflon-lined stainless steel autoclave and reacted at 200 °C for 5 hours. After that, the sample was collected by centrifugation and completely dried. The final product was washed several times with water and anhydrous ethanol and vacuum dried at 60 °C for 24 hours. Finally, it was treated in high-purity argon at 300 °C for 1 hour to obtain Fe-anchored single-layer CuInP2S6 nanosheets, and the content of Fe atoms in the single-layer CuInP2S6 nanosheets was 1.8%.
[0041] The prepared Fe-anchored single-layer CuInP2S6 nanosheets were tested for hydrogen evolution performance. When the hydrogen adsorption free energy was close to zero, the catalyst had better hydrogen evolution reaction performance. Figure 2 As shown, the calculation results show that the hydrogen evolution performance of the anchored single-layer CuInP2S6 nanosheet is significantly improved. For the system with Fe anchored on the lower surface, the hydrogen adsorption free energy is 0.05eV. Example 2
[0042] High-quality bulk CuInP2S6 was synthesized by solid-state reaction. 10 mg of the synthesized bulk was dispersed in 30 mL of deionized water and ultrasonicated for 6 h, after which the supernatant was collected. The obtained liquid was dried at 70 °C for 40 h to obtain a single-layer CuInP2S6 nanosheet. 10 mg of single-layer CuInP2S6 nanosheets were dissolved in 20 mL of deionized water by ultrasound, and then 0.06 mL of 3 mg / mL CrCl3 aqueous solution was added to the solution and stirred thoroughly. The obtained mixed solution was transferred to a Teflon-lined stainless steel autoclave and reacted at 200 °C for 5 hours. After that, the sample was collected by centrifugation and completely dried. The final product was washed several times with water and anhydrous ethanol and vacuum dried at 60 °C for 24 hours. Finally, it was treated in high-purity argon at 300 °C for 1 hour to obtain Cr-anchored single-layer CuInP2S6 nanosheets, and the content of Cr atoms in the single-layer CuInP2S6 nanosheets was 1.8%.
[0043] The hydrogen evolution performance of the prepared Cr-anchored single-layer CuInP2S6 nanosheets was tested. When the hydrogen adsorption free energy is close to zero, the hydrogen evolution reaction performance of the catalyst is better. Figure 2 As shown, the calculation results show that the hydrogen evolution performance of the anchored single-layer CuInP2S6 nanosheet is significantly improved. For the system with Cr anchored on the lower surface, the hydrogen adsorption free energy is 0.11eV. Example 3
[0044] The only difference from Example 1 is that Mn is used to anchor the single-layer CuInP2S6 nanosheet, and the content of Mn atoms in the single-layer CuInP2S6 nanosheet is 1.8%.
[0045] The hydrogen evolution performance of the prepared Mn-anchored single-layer CuInP2S6 nanosheets was tested. When the hydrogen adsorption free energy is close to zero, the hydrogen evolution reaction performance of the catalyst is better. Figure 2 As shown, the calculation results show that the hydrogen evolution performance of the anchored single-layer CuInP2S6 nanosheet is significantly improved. For the system with Mn anchored on the lower surface, the hydrogen adsorption free energy is 0.29eV. Example 4
[0046] The only difference from Example 1 is that Co is used to anchor the single-layer CuInP2S6 nanosheet, and the content of Co atoms in the single-layer CuInP2S6 nanosheet is 1.8%.
[0047] The prepared Co-anchored single-layer CuInP2S6 nanosheets were tested for hydrogen evolution performance. When the hydrogen adsorption free energy is close to zero, the catalyst has better hydrogen evolution reaction performance. Figure 2 As shown, the calculation results show that the hydrogen evolution performance of the anchored single-layer CuInP2S6 nanosheet is significantly improved. For the system with Co anchored on the lower surface, the hydrogen adsorption free energy is 0.24eV. Comparative Example 1
[0048] High-quality bulk CuInP2S6 was synthesized by solid-state reaction. 10 mg of the synthesized bulk was dispersed in 30 ml of deionized water and ultrasonicated for 6 hours, after which the supernatant was collected. The obtained liquid was dried at 70°C for 40 hours to obtain a single-layer CuInP2S6 nanosheet.
[0049] The hydrogen evolution performance of the prepared single-layer CuInP2S6 nanosheet was tested. When the hydrogen adsorption free energy is close to zero, the hydrogen evolution reaction performance of the catalyst is better. Figure 1 As shown, the calculated results show that the hydrogen adsorption free energy of the unanchored single-layer CuInP2S6 nanosheet is 0.94 eV. Comparative Example 2
[0050] The only difference from Example 1 is that Ni is used to anchor the single-layer CuInP2S6 nanosheet, and the content of Ni atoms in the single-layer CuInP2S6 nanosheet is 1.8%.
[0051] The prepared Ni-anchored single-layer CuInP2S6 nanosheets were tested for hydrogen evolution performance. When the hydrogen adsorption free energy is close to zero, the catalyst has better hydrogen evolution reaction performance. Figure 2 As shown, the calculation results show that for the system with Ni anchored on the lower surface, the hydrogen adsorption free energy is 0.96 eV.
[0052] It can be seen from the above examples that, under the premise of ensuring that the catalyst has good stability, the transition metal anchoring in the examples generally improves the hydrogen evolution performance; and among the many transition metal anchored samples, the anchoring of Fe has the greatest impact on the hydrogen evolution performance. For the field of photocatalytic hydrogen evolution, a lower hydrogen adsorption free energy, a simple preparation process and good stability are the characteristics of an ideal catalyst. The transition metal anchored single-layer CuInP2S6 nanosheet of the present invention has these characteristics and is expected to become an ideal photocatalytic hydrogen evolution catalyst.
[0053] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a transition metal-anchored single-layer CuInP2S6 nanosheet, characterized in that: The following steps are involved: 1) Mixing a single-layer CuInP2S6 nanosheet dispersion with a transition metal salt solution, and performing a hydrothermal reaction to obtain an intermediate product; 2) The intermediate product is calcined under a protective atmosphere to obtain a transition metal-anchored single-layer CuInP2S6 nanosheet.
2. The method for preparing a transition metal-anchored single-layer CuInP2S6 nanosheet according to claim 1, characterized in that: The single-layer CuInP2S6 nanosheet dispersion is prepared by dispersing the single-layer CuInP2S6 nanosheet in water; the dosage ratio of the single-layer CuInP2S6 nanosheet to water is 8-12 mg: 20 mL.
3. The method for preparing a transition metal-anchored single-layer CuInP2S6 nanosheet according to claim 2, characterized in that: The concentration of the transition metal salt solution is 1-5 mg / mL; The usage ratio of the transition metal salt solution and the single-layer CuInP2S6 nanosheet is 0.01-0.1 mL: 10 mg.
4. The method for preparing a transition metal-anchored single-layer CuInP2S6 nanosheet according to claim 3, characterized in that: The anchoring amount of the transition metal atoms in the single-layer CuInP2S6 nanosheet is 1-2%.
5. The method for preparing a transition metal-anchored single-layer CuInP2S6 nanosheet according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 160-240°C and the time is 3-8 hours.
6. The method for preparing a transition metal-anchored single-layer CuInP2S6 nanosheet according to claim 1, characterized in that: The protective atmosphere comprises argon, nitrogen or helium; The calcination temperature is 3-8 °C / min, the temperature is 200-400 °C, and the calcination time is 0.5-3 h.
7. The method for preparing a transition metal-anchored single-layer CuInP2S6 nanosheet according to claim 1, characterized in that: The single-layer CuInP2S6 nanosheet dispersion and the transition metal salt solution are mixed at room temperature for 4 to 8 hours.
8. The method for preparing a transition metal-anchored single-layer CuInP2S6 nanosheet according to claim 3, characterized in that: The transition metal salt solution comprises a transition metal chloride salt solution or a transition metal acid salt solution.
9. Transition metal-anchored single-layer CuInP2S6 nanosheets prepared by the method for preparing transition metal-anchored single-layer CuInP2S6 nanosheets according to any one of claims 1 to 8.
10. Use of the transition metal-anchored single-layer CuInP2S6 nanosheets according to claim 9 in a photocatalytic hydrogen evolution catalyst.
Citation Information
Patent Citations
Monatomic catalyst as well as preparation method and application thereof
CN112221528A
CuInP2S6-based heterojunction photocatalyst with 2D / 2D structure and preparation method of CuInP2S6-based heterojunction photocatalyst
CN115672361A
Two-dimensional ferroelectric monatomic Ag loaded electrocatalyst
CN116516394A
Monoatom-modified ultrathin sulfur indium zinc nanosheet as well as preparation method and application thereof
CN118162163A
Cited By
Transition metal nitride CuInP2Nx, preparation method and application
CN121653708A